Quantitative proteomics of differentiated primary bronchial epithelial cells from chronic obstructive pulmonary disease and control identifies potential novel host factors post-influenza A virus infection - Nakayama, Misako; Marchi, Hannah; Dmitrieva, Anna M.; Chakraborty, Ashesh; Merl-Pham, Juliane; Hennen, Elisabeth; Le Gleut, Ronan; Ruppert, Clemens; Guenther, Andreas; Kahnert, Kathrin; Behr, Jürgen; Hilgendorff, Anne; et al. (Frontiers in Microbiology, 2023)
Background: Chronic obstructive pulmonary disease (COPD) collectively refers to chronic and progressive lung diseases causing irreversible limitations in airflow. COPD patients are at high risk for severe respiratory symptoms upon influenza virus infection. Airway epithelial cells provide the first-line antiviral defense, but whether their susceptibility and response to influenza virus infection changes in COPD has not been elucidated. Therefore, this study aimed to i) compare the susceptibility of COPD- and control-derived airway epithelium to influenza virus, and ii) assess protein changes during influenza virus infection by quantitative proteomics. Methods: Presence of human- and avian-type influenza A virus receptor was assessed in control and COPD lung sections as well as in fully differentiated primary human bronchial epithelial cells (phBECs) by lectin- or antibody-based histochemical stainings. PhBECs were from COPD lungs, including cells from moderate and severe disease stages, and from age-, sex-, and smoking history-matched control lung specimens. Protein profiles pre- and post-influenza virus infection in vitro were directly compared using quantitative proteomics, and selected findings validated by qRT-PCR and immunoblotting. Results: The human-type influenza receptor was more abundant in human airways than the avian-type influenza receptor, a property that was retained in vitro when differentiating phBECs at the air-liquid interface. Proteomics of phBECs pre- and post-influenza A virus infection with A/Puerto Rico/8/34 (PR8) revealed no significant differences between COPD and control phBECs in terms of flu receptor expression, cell type composition, virus replication, or protein profile pre- and post-infection. Independent of health state, a robust antiviral response to influenza virus infection was observed, as well as upregulation of several novel influenza virus-regulated proteins including PLSCR1, HLA-F, CMTR1, DTX3L, and SHFL. Conclusions: COPD-derived and control-derived phBECs did not differ in cell type composition, susceptibility to influenza virus infection, and proteomes pre- and post-infection. Finally, we identified novel influenza A virus-regulated proteins in bronchial epithelial cells that might serve as potential targets to modulate pathogenicity of infection and acute exacerbations.